Pengaruh Kedisiplinan Terhadap Kinerja Karyawan Melalui Kompensasi Pada Koperasi Karyawan PT. Kawasan Berikat Nusantara (Persero) - Diana Noviyanti; Supardi Supardi; Agus Dharmanto (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to find out whether discipline has an effect on employee performance through compensation. The method used in this research is a quantitative method. The population in this study were all employees at the PT Employee Cooperative. Archipelago Bonded Zone (Persero). Determining the sample in this study used a saturated sampling technique, namely the entire population was sampled, amounting to 100 employees. Data were analyzed using SPSS 25. The methods used were validity test, reliability test, normality test, t test, and path analysis test. The research results show that discipline has an influence on compensation, compensation has an influence on employee performance, discipline has an influence on employee performance. The results of the path analysis test are Discipline on Employee Performance through Compensation at the PT Employee Cooperative. Archipelago Bonded Zone (Persero)